Nonsyndromic supernumerary bilateral parapremolars - Vineeta Singhal; D Deepa (Wolters Kluwer Medknow Publications, 2017)
Supernumerary teeth are a rare finding in dental arch, which are mostly reported in association with syndromes. However, they can be seen in the absence of systemic disease. They may be single, multiple, unilateral, or bilateral with a predilection for the mandible, especially in nonsyndromic patients. Due to its different form and position in dental arch, it is observed to be associated with various periodontal problems. This case report presents a case of bilateral parapremolars in the maxillary arch in a nonsyndromic patient, which led to food lodgment and consequently led to caries and periodontal problem on the left maxillary arch.